Implementasi Pengusiran Roh Jahat oleh Tuhan Yesus menurut Markus 9:14-29 bagi Pelayanan Okultisme Di LPPS Palu - Yatafati Zebua (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the implementation of exorcism by Jesus Christ according to Mark 9:14-29 and its relevance to occult ministry at LPPS Palu. Through exegetical study, it is found that the power and authority of Jesus in casting out evil spirits emphasize the importance of faith and prayer as the main keys in similar ministries. The inability of Jesus’ disciples to cast out the evil spirit in this pericope serves as a reflection for contemporary ministry, which often also experiences failure due to a lack of faith and dependence on God. This article highlights the need for a proper understanding of the distinction between medical disorders and manifestations of dark powers, and affirms that exorcism should be carried out with authority in the name of Jesus. The practical implication of this research is the importance of strong spiritual preparation, faith, and a consistent prayer life in occult ministry within the church environment.